Is Collaborative, Community-Engaged Scholarship More Rigorous Than Traditional Scholarship? On Advocacy, Bias, and Social Science Research. (April 2018) - Warren, Mark R.; Calderón, José; Kupscznk, Luke Aubry; Squires, Gregory; Su, Celina
Contrary to the charge that advocacy-oriented research cannot meet social science research standards because it is inherently biased, the authors of this article argue that collaborative, community-engaged scholarship (CCES) must meet high standards of rigor if it is to be useful to support equity-oriented, social justice agendas. In fact, they argue that CCES is often more rigorous than traditional scholarship. The authors draw from cases of CCES that they conducted to provide evidence and examples. They discuss the importance of relationship building and trust in addressing the tensions that can arise between the demands of knowledge production and action-oriented social change.